Java / An Introduction to Computer Science & Programming - Savitch, Walter J. (Prentice Hall, 1999)
Introduction and a Taste of Java, Primitive Types and Strings, Flow of Control, Classes and Objects and Methods, Programming with Classes and Methods, Inheritance, Event-Driven Programming Using the AWT, Exception Handling, Streams and File I/ O, Arrays, Multimensional Arrays and Vectors, Recursion, Applets and HTML, Index.